The Islamic influence in moulding and shaping the Vienna convention on diplomatic relations 1961 - Elshobake, Mohammed R. M.; Maidin, Mohamed Hanipa (IIUM Press, 2024)
This paper seeks to discuss the origin of diplomacy in international law and its gradual development from its infancy phase until the official emergence of the Vienna Convention on Diplomatic Relations 1961 (“VCDR 1961”), as well as the challenges faced by the global players of international law in ensuring that international diplomacy, as embodied in the VCDR 1961, is invariably adhered to. It also highlights the prominent principles of diplomacy in Islam and their practical examples. This paper employs a descriptive-analytical approach, which contributes significantly to the study of the topic of Islamic influence in moulding and shaping the Vienna Convention on Diplomatic Relations 1961. The centrality of this paper resides in the elaboration of the enormous influence of Islamic law of diplomacy on the VCDR 1961 and well-established state practice (which is a rule of Customary law). However, the focus is more on the Islamic influences that have permeated the VCDR 1961.